Biomarkers of Ovarian Reserve—Do They Predict Somatic Aging? - Cedars, Marcelle I. (Seminars in Reproductive Medicine, 2013)
Menopause, while the end of reproduction, also represents a major hormonal, psychological and physiological event in the lives of all women. Several studies have suggested an association between the age of menopause and longevity. Additionally, cellular and molecular mechanisms of general aging have been suggested to play a vital role in ovarian aging. In parallel with the recognition of these similar physiological parameters, markers of “ovarian age,” also known as ovarian reserve, have been developed. These markers may allow prediction of age of menopause and the identification of women at increased risk for earlier menopause, and perhaps advanced somatic aging. The ability to identify these women would be critically important if decreased ovarian reserve were associated with increased long-term health risks. Thus, it is critical to understand if ovarian aging, and particularly, early ovarian aging, would place women at risk for long-term health issues with increased morbidity and mortality. Numerous studies reviewed support an association between menopause, and premenopausal changes consistent with diminish ovarian reserve, and cardiovascular risk, bone loss and changes in mood and cognition. Only longitudinal studies will be able to confirm if any identified associations reflect causality or common underlying risk, but the available data suggest women with diminished ovarian reserve represent a unique group that may be at increased risk for long-term health effects beyond fertility loss.
Keywords: ovarian aging; somatic aging; oxidative stress; mitochondrial function and aging